Analysis of CYP701A1 genes in gossypium species and functional characterization through gene silencing - Zhao Liang; Di Jiachun; Guo Qi; Xu Zhenzhen; Zhao Jun; Xu Peng; Xu Jianwen; Liu Jianguang; Shen Xinlian; Chen Xusheng (Crop Design)
Gibberellins (GA) are known to play crucial roles in various aspects of plant growth and development. The cytochrome P450 enzyme family is recognized for its significance in plant metabolic processes. Specifically, CYP701s, a subgroup of CYP71, encode ent-kaurene oxidase in the gibberellin synthesis pathway. In this study, we analyzed genomic data from 30 Gossypium species, including nine allotetraploid genomes (AD1-AD7, with two each for AD1 and AD2), 21 diploid genomes (A-G, K, with two A-genomes and 12 D-genomes), and Gossypioides kirkii genome as an outgroup for evolutionary analysis, totaling 31 genomes. Subsequently, 40 CYP701A1 genes were identified from various genomes and conducted a comprehensive analysis of their structure and evolution. Virus-induced gene silencing (VIGS) technology was utilized to knock out the GhCYP701A1 gene in Gossypium hirsutum ac TM-1. Subsequent analysis revealed changes in hormone content, with decreased gibberellin levels and notable increases in auxin, cytokinin, and jasmonic acid contents. Conversely, salicylic acid content decreased, while the precursor for ethylene synthesis, 1-aminocyclopropane-1-carboxylic acid (ACC), remained relatively stable. Transcriptome analysis of the gene silencing plants identified 15,962 differentially expressed genes, including 8376 upregulated and 7586 downregulated genes. Enrichment analysis through KEGG pathway highlighted ‘Plant hormone signal transduction’ as a prominent pathway with 234 differentially expressed genes. The study provided insights into the function and regulatory network of the gene.